ANALISIS INDUSTRI BATIK DALAM PENGELOLAAN LIMBAH DALAM UPAYA SUSTAINABLE DEVELOPMENT GOALS (SDGS) DI PROVINSI JAMBI - Rafidah, M. Yunus (LPSDI Bina Patria, 2023)
Batik Jambi is a local product which is one of the characteristics possessed by Jambi Province which is spread across various Jambi districts/cities. The resulting products use chemicals and natural ingredients in the coloring process. The use of chemicals will certainly have an impact on the surrounding environment if waste management is not managed properly. This impact will be very dangerous for the surrounding environment and the preservation of the earth in maintaining the Sustainable Development Goals (SDGs). The purpose of this study was to find out the batik craftsmen's understanding of batik waste management and the application of batik waste management by conducting in-depth interviews with 14 business units, both Jambi and related agencies. The results showed that the understanding of the batik craftsmen was very good due to the socialization and education that had been given but in the implementation in the field there were still obstacles because the assistance of an IPAL machine for a group of artisans could not be used optimally, the limited capital factor to make Household IPAL, the location very small business, business is not grouped so it is very difficult to get help to make IPAL. The role played by the government has been quite optimal by providing socialization and education but still has to maximize this effort by continuing to carry out counseling and socialization about methods that can be applied to handle industrial waste, counseling on the use and maintenance of appropriate technology and green technology, making household scale IPAL, optimizing the government's budget, establishing a policy of sanctioning environmental polluters through government regulations, batik craftsmen are required to make private or group IPAL, including environmental costs charged to the batik products they produce.